Resisting the Idealised 'healthy lifestyle': Medical Mavericks, Fat Activists, and Couch Potatoes in U.S. and Dutch Newspapers (1967-1989). (8th August 2021) - Verriet, Jon
ABSTRACT: In the past, advice on healthy living has often been neglected, or even openly defied. However, despite the prevalence of historical resistance against an idealised healthy lifestyle, this phenomenon has seen minimal investigation. Using eight American and Dutch newspapers, this study analyses how various 'resisters' found cross-border recognition from journalists for challenging existing norms about diet and exercise. It demonstrates that in the post-war era, lifestyle advice was increasingly contested in the U.S. and the Netherlands, leading to a transnational cacophony on the topic of health, and an increasingly ambiguous role for medical experts.